Interprofessional Collaboration In Diagnostic Imaging And Patient Care: Role Integration, Communication Frameworks, And Quality Improvement Outcomes (The Review of Diabetic Studies, 2024)
Diagnostic imaging services represent a critical component of modern healthcare delivery, requiring seamless coordination among multiple healthcare professionals including radiological technologists, health informatics specialists, nurses, psychologists, and administrative personnel. This comprehensive review examines the evidence surrounding interprofessional collaboration (IPC) in diagnostic imaging environments, focusing on role integration, communication frameworks, and their impact on patient outcomes and healthcare quality. A systematic review of peer-reviewed literature published between 2015 and 2025 was conducted using multiple databases to identify studies examining interprofessional teams in medical imaging settings, communication effectiveness, patient safety, and quality improvement initiatives. The review identified 47 relevant studies addressing various dimensions of interprofessional practice in radiology and imaging services. Evidence demonstrates that structured interprofessional collaboration significantly improves patient care quality, reduces diagnostic errors, enhances patient satisfaction, and optimizes workflow efficiency in imaging departments. Key findings indicate that effective communication protocols, clearly defined role responsibilities, and shared decision-making processes are essential elements of successful interprofessional teams. Furthermore, the integration of health informatics systems facilitates information sharing and coordination among team members. Implementation of interprofessional education, training programs, and collaborative practice models shows promising results in enhancing team performance and patient outcomes. This review highlights the critical importance of fostering a culture of collaboration in diagnostic imaging services and provides recommendations for healthcare administrators, educators, and policy makers to support interprofessional teamwork. Continued investment in interprofessional training, supportive organizational structures, and technology infrastructure is essential to optimize diagnostic imaging services and enhance the overall quality of patient care.